INSTRUCTIONAL GUIDE TO SUBSIDIZE THE NURSING CONSULTATION IN LOW-RISK PRENATAL CARE: CONSTRUCTION AND VALIDATION - Teixeira, Wanderson Luís; Zocche, Denise Antunes de Azambuja; Zanotelli, Silvana dos Santos; Martins, Maria Fátima Silva Vieira; Backes, Dirce Stein (Cogitare Enfermagem, 2023)
Objective: to develop a technical guide for low-risk prenatal care. Method: methodological research that included the construction and validation of a technical guide. A questionnaire and two bibliographic reviews were applied in data collection. Conducted in the macro regions of the Great West and Midwest of Santa Catarina - Brazil. For the construction of the guide, we had an exploratory stage with 48 nurses. Results: the guide consists of three chapters. Nursing care in low-risk prenatal care. The nursing consultation and the appropriate management according to the gestational period. Protocols, instruments, and scales used in low-risk prenatal care. Validation was performed by 14 judges with Content Validity Index 0.96. Conclusion: the guide will contribute to the qualification of nurses' work in Primary Health Care, transforming the obstetric scenario of the regions involved and strengthening nurses' practices in the performance of low-risk prenatal care.